2020
DOI: 10.1186/s12859-020-3436-7
|View full text |Cite
|
Sign up to set email alerts
|

MMiRNA-Viewer2, a bioinformatics tool for visualizing functional annotation for MiRNA and MRNA pairs in a network

Abstract: Background: Although there are many studies on the characteristics of miRNA-mRNA interactions using miRNA and mRNA sequencing data, the complexity of the change of the correlation coefficients and expression values of the miRNA-mRNA pairs between tumor and normal samples is still not resolved, and this hinders the potential clinical applications. There is an urgent need to develop innovative methodologies and tools that can characterize and visualize functional consequences of cancer risk gene and miRNA pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Biclustering solutions can be represented using graphs with observations and attributes represented as nodes [ 158 , 167 , 168 ]. Biclusters are then represented either by labeled edges in a graph ( Figure 22 ) or by a shaded area ( Figure 23 ).…”
Section: Evaluation Measuresmentioning
confidence: 99%
“…Biclustering solutions can be represented using graphs with observations and attributes represented as nodes [ 158 , 167 , 168 ]. Biclusters are then represented either by labeled edges in a graph ( Figure 22 ) or by a shaded area ( Figure 23 ).…”
Section: Evaluation Measuresmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a type of small noncoding RNAs with a length of about 19–25nt, , participate in various cellular processes such as cell formation, differentiation, proliferation, and apoptosis. , Most miRNAs interact with the 3′ untranslated region (3′ UTR) of target mRNAs to induce their degradation and translational repression. In recent years, many studies have shown that miRNAs play a non-negligible role in the regulation of drug response among different cancers. ,, Especially, some miRNAs are potential therapeutic targets to enhance drug sensitivity. For example, inhibition of miR-21 and miR-200b can increase sensitivity to Gemcitabine in human cholangiocarcinoma cells . Upregulation of miR-155-5p enhanced the sensitivity of liver carcinoma cells to Adriamycin and promoted apoptosis through the inhibition of autophagy in vitro .…”
Section: Introductionmentioning
confidence: 99%